Behavioral Correlates of Fruit and Vegetable Intake in Puerto Rico: Results from the Health Information National Trends Survey - Colón-López, Vivian; Banerjee, Geetanjoli; Gertz, Alida María; Ortiz, Ana Patricia; Calo, William; Finney-Rutten, Lila J.; Colón-Ramos, Uriyoán; Hesse, Bradford W.; Tortolero, Guillermo (Puerto Rico Health Sciences Journal, 2013)
Objective: A diet high in fruit and vegetables (FV) is associated with a decreased risk for chronic diseases, such as cancer. Limited information exists regarding the factors associated with FV intake in persons living in Puerto Rico. The objective of this study was to examine sociodemographic, behavioral, and health belief factors associated with dietary habits in Puerto Rico. Methods: Secondary data analysis of adults aged 18 years and older from the Puerto Rico Health Information National Trends Survey (HINTS-PR) conducted in 2009. Multivariate logistic regression models were used to identify factors associated with meeting the established recommendations for FV consumption. Results: Only 14.5% of the adults in Puerto Rico met the recommendations for daily FV intake, and the vast majority (90.9%) were unaware of current recommendations. Bivariate analyses demonstrated that being obese, having lower than a high school education, and not knowing the recommendations were significantly associated with not meeting these recommendations. In the multivariate logistic regression analysis, being obese (OR = 3.77; 95% CI = 1.41-10.08) and not being aware of the current dietary recommendations (OR = 9.26; 95% CI = 3.77-22.73) continued to be significantly associated with not meeting the FV intake recommendations. Conclusion: The Puerto Rican population is far from meeting FV consumption recommendations, with prevalence estimates of consumption that are below the US median. Low FV intake might put the population in Puerto Rico at increased risk of developing cancer as well as a number of other chronic diseases that are secondary both to improper nutrition and to obesity.